China's Belt and Road Initiative: Implications for intra‐regional trade in Africa. Issue 1 (27th August 2020) - Kalu, Kenneth; Farrell, Carlyle; Lin, Xiaohua
Abstract : This paper considers the prospects and promises of continent‐wide infrastructure projects under China's Belt and Road Initiative (BRI), and its implications for intra‐regional trade and economic development in Africa. Building on the supply side theory of trade and economic development, and taking cognizance of the impacts of asymmetric market sizes on trade integration, this paper argues that continent‐wide infrastructure projects are perhaps not the biggest constraints to intra‐Africa trade. Consequently, the paper recommends caution in pursuing regional infrastructure projects under the BRI. Given that the economies of most African countries depend largely on natural resources, the BRI could be adopted strategically to establish and manage infrastructure projects that would relax the binding constraints to structural transformation and allow for the development of manufacturing and/or service capabilities in the respective countries, especially in niche areas.